EP247 Sarcopenia is really prognostic factor of outcome in patients with cervical cancer with concurrent chemoradiotherapy?. (1st November 2019) - Arakaki, Y; Shimoji, Y; Nakasone, T; Taira, Y; Nakamoto, T; Ooyama, T; Kudaka, W; Aoki, Y
Abstract : Introduction/Background: This study aimed to reveal that pre-treatment sarcopenia is really a prognostic factor of outcome with patients undergoing concurrent chemoradiotherapy (CCRT) in cervical cancer. Methodology: We retrospectively analyzed pre-treatment CT images of 115 patients with cervical cancer who were treated by same regimen and same irradiation range between 2010 to 2015. All CT images were taken within 30days before radiotherapy. Skeletal muscle index (SMI) was calculated from CT images at the level of third lumbar vertebra, in the range from -29 to +150 Hounsfield Units. We defined sarcopenia as low SMI (less than 38.5cm 2 /m 2 ). Overall survival (OS) and disease free survival (DFS) were analyzed Kaplan-Meier method and Cox hazard regression model. Results: The median follow-up was 46 months(range, 2–104 months). 65 patients (56.5%) was defined pre-treatment sarcopenia. The median DFS was 42 months (range, 0–104 months). Sarcopenia was not poorer prognostic factor for PFS and OS rates (p=0.4915, and p=0.5811). Multivariate analysis showed same results. Conclusion: Pre-treatment sarcopenia was not prognostic factor for patients with cervical cancer who treated with CCRT. Disclosure: Nothing to disclose.